Governance In Developing Village Tourism And Focus Of Mawar Picking In Batu City - Lilik Purwanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
BUM Desa is business entities whose almost all of the capital is owned by the Village through investment. BUM Desa Sejahtera Gunungsari has been formed since 2018. Gunungsari Village has the tourism potential of Picking Roses, land of lanterns and cultural arts. The problem are not ready the organization's management, business management strategies, tourism promotion, marketing and accountability system. The method used by the PAR and Strategic Management approach with 4 stages. The solutions are emphasized on environment observation and strategy formulation. Therefore it is necessary to develop an appropriate BUM Desa management model for Tourism Villages which consists of a management system, financial management, and governance of promotion and marketing. The application of financial management uses the BUM Desa Accounting Application System which must be supported by improving the knowledge and skills of BUM Desa administrators.